Investigation of Toxin Genes by Polymerase Chain Reaction in Staphylococcus aureus Strains Isolated from Bovine Mastitis in Turkey - Karahan, Murat; Acik, Mehmet Nuri; Cetinkaya, Burhan (Mary Ann Liebert, Inc, 2009)
Staphylococcus aureus causes a number of diseases in humans and animals, and it is the most common etiological agent of contagious bovine mastitis. The agent produces several virulence factors such as coagulase (coa), clumping factor, protein A, exfoliative toxins, staphylococcal enterotoxins (SEs), and toxic shock syndrome toxin-1. The aim of the present study was to characterize coa-positive S. aureus strains (n = 92) isolated from bovine subclinical mastitis in Turkey by polymerase chain reaction (PCR) amplification of exfoliative toxin (eta and etb) and toxic shock syndrome toxin-1 (tsst) genes. In addition, a multiplex PCR was employed to investigate the presence of SE genes sea, seb, sec, sed, see, seg, seh, sej, and sei. By PCR amplification, while eta and etb were not detected, only three isolates (3.3%) were positive for tsst. Twenty-seven (29.3%) isolates harbored one or more SE genes, and sei was the most common pattern by multiplex PCR. None of the isolates harbored the genes encoding sea, see, and seh. The application of this multiplex PCR assay could enable more samples to be rapidly characterized for enterotoxin production of S. aureus isolates from milk for epidemiological studies.
Keywords: Shock-Syndrome Toxin-1; Enterotoxin Genes; Multiplex Pcr; Milk; Cows; Pathogens; Identification; Polymorphisms; Exotoxins; Samples